1996
DOI: 10.1007/bf01718633
|View full text |Cite
|
Sign up to set email alerts
|

Immunological response of mice to the bovine respiratory syncytial virus fusion glycoprotein expressed in recombinant baculovirus infected insect cells

Abstract: Bovine respiratory syncytial virus (BRSV) is a major cause of respiratory disease in calves. The BRSV genome encodes two major glycoproteins, G and F, which are the major targets for the host antibody response. We have expressed the F glycoprotein in insect cells (Sf9) using a recombinant baculovirus vector. A comparison of the F protein expressed in mammalian and insect cells by SDS-PAGE showed that only part of the baculovirus-produced protein was soluble and processed like the native protein. The antigenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mammalian cell-expressed gp120 contained the expected proportions of complex and high-mannose glycans, implying that the purification process did not impose any dramatic bias in the selection of glycan types on the different glycoprotein forms. It has been reported that insect cell-expressed material may have reduced numbers of glycans due to sequon skipping11; 12. Reduced numbers of glycans would be expected to modify the antigenicity of a highly-glycosylated protein, and might also influence immunogenicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian cell-expressed gp120 contained the expected proportions of complex and high-mannose glycans, implying that the purification process did not impose any dramatic bias in the selection of glycan types on the different glycoprotein forms. It has been reported that insect cell-expressed material may have reduced numbers of glycans due to sequon skipping11; 12. Reduced numbers of glycans would be expected to modify the antigenicity of a highly-glycosylated protein, and might also influence immunogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…High-mannose glycans occur more frequently in the conserved regions, whereas those attached to variable loops, being more exposed to the glycosylation machinery of the Golgi, are more frequently processed into complex glycans6; 9. Conversely, in wild-type insect cell systems glycosylation is restricted to paucimannosidic structures10 and the degree of sequon occupancy may be lower11; 12.…”
mentioning
confidence: 99%